KAJIAN SOSIAL EKONOMI YANG MEMPENGARUHI KEMISKINAN PETANI (Studi Kasus : Kecamatan Payung Kabupaten Karo) - Syaifuddin Syaifuddin (JURNAL AGRICA, 2016)
The aimed of this study was to determine the correlation of capital, age, land use, education level and number of dependents on poverty of farming communities in the study area, as well as determine the level of poverty of farming communities in the study area. The study was conducted in the Payung Village, Payung sub-district, Karo District, North Sumatra Province. The method used purposive sampling with 37 sample farmers household and rank-Spearman Corellation. The results showed that the factor of capital, land area and the number of dependents significantly correlated with the level of poverty of farmers, while age and education level did not correlate significantly. Based on the rice consumption in general is still relatively poor families and poor once.Keyword : Social Economic, poverty, farmers